2015
DOI: 10.1590/1678-7153.201528215
|View full text |Cite
|
Sign up to set email alerts
|

Phonemic and semantic verbal fluency tasks: normative data for elderly Brazilians

Abstract: This study aims to investigate the infl uence of sociodemographic characteristics on the performance of older people on two tasks of verbal fl uency and provide normative data for a Brazilian population of healthy elderly individuals with different educational levels. The initial sample included 521 individuals aged from 60 years, participating in the Program Family Health Strategy. Participants who had scores suggestive of cognitive decline on the Mini-Mental State Examination, depressive symptoms in Geriatri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0
8

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 27 publications
1
32
0
8
Order By: Relevance
“…The instrument also includes the Verbal Fluency (VF) test – animals category, and Clock Drawing Test (CDT), applied between the third recall of drawings and delayed recall. 6 , 7 Previous studies on the Figure Memory Test of the BCSB have shown little influence of education, 7 while the CDT 8 , 9 and VF test 10 , 11 appear to be more influenced by education.…”
Section: Introductionmentioning
confidence: 85%
“…The instrument also includes the Verbal Fluency (VF) test – animals category, and Clock Drawing Test (CDT), applied between the third recall of drawings and delayed recall. 6 , 7 Previous studies on the Figure Memory Test of the BCSB have shown little influence of education, 7 while the CDT 8 , 9 and VF test 10 , 11 appear to be more influenced by education.…”
Section: Introductionmentioning
confidence: 85%
“…on the cognitive reserve, since the years of study are directly related to a greater cognitive reserve, indicating a strong influence of schooling on the results of the verbal fluency test 11,23 . This hypothesis is reinforced by a national study aiming to establish normative standards for verbal fluency tests, in which the authors 24 observed that the educational variable showed a greater impact, in both evocation modalities, than age.…”
Section: Resultsmentioning
confidence: 99%
“…O objetivo do estudo foi gerar normas para estes testes e avaliar o impacto das variáveis sociodemográficas em seus resultados. Tanto idade como escolaridade puderam ser consideradas como influentes para os resultados em ambos os TFVs, no entanto, assim como em outros estudos, a escolaridade causava impacto mais contundente (ESTEVES et al, 2015).…”
Section: Lista De Tabelasunclassified
“…Quando os resultados do TFV são comparados com outros estudos é possível notar um desempenho acima da maioria dos já relatados, principalmente quando os grupos são pareados por idade e escolaridade (NITRINI et al, 1994;BRUCKI et al, 1997;ARGIMON & STEIN, 2005;PEREIRA et al, 2010;SILVA et al, 2011;GUIMARÃES et al, 2014;ESTEVES et al, 2015;BORGES-LIMA, ALVES et al, 2017). Os gráficos de 12 a 19 apresentam as comparações entre os resultados do TFV do presente estudo e outros estudos agrupados por escolaridade e faixa etária.…”
Section: C Estudo Do Efeito Da Escolaridade Na Bbrcunclassified
See 1 more Smart Citation